Budget 2019: tax and welfare changes - Roantree, Barra (The Economic and Social Research Institute, 2018)
In his budget delivered to the Dáil on 9 October, the Minister for Finance, Public Expenditure and Reform announced an increase in General Government expenditure for 2019 of €4.2 billion, an increase of 5.1 per cent from its 2018 level. This is to be financed by a small General Government deficit of €75 million. The majority of this additional expenditure was allocated to capital investment and public services, but the government also announced a number of changes to the tax and social welfare system in 2019: €711 million in tax increases, €370 million in tax cuts and €362 million in increased transfers. However, this excludes discretionary tax increases announced in the Summer Economic Statement which are expected to raise a further €600 million. This article describes and assesses these reforms, first looking at the main taxation measures announced in the budget, before going on to examine the social welfare measures. It then considers the effect of these measures as a whole on the incomes of households using representative survey data and SWITCH, the ESRI’s tax and benefit microsimulation model. The article concludes with some brief reflections on some of the fiscal challenges facing the government in the coming years.
PUBLISHED
Keywords: Inclusive Society